A associação entre o polimorfismo RSAI do gene receptor-beta de estrógeno com a infertilidade masculina - Bordin, Bárbara Mariotto (2009)
Oestrogen Receptor (ER ) gene plays an important role in the regulation of fertility in both males and females. The RsaI polymorphism in exon 5 of ER has been shown to be associated with male infertility in Caucasian patients. The aim of this study was to investigate the frequency of this polymorphism in the etiology of idiopathic male infertility and to correlate with smoking and ethylism habits, xenobiotic contact and mumps. We analyzed 287 Brazilian men, including 161 infertile and 126 fertile men to evaluate the association of RsaI polymorphism in male infertility. The RsaI variant alleles (AA, AG or GG) of the patients were determined by allele-specific polymerase chain reaction. Compared with a control group (normozoospermic men), the frequency of the heterozygous RsaI AG-genotype was four times higher in infertile men (9,94 vs. 2,38%; P = 0,01), five times higher in azoospermic men (11,36 vs. 2,38%; P = 0,02) and seven times higher in teratozoospermic men ( 17,79 vs. 2,38%; P = 0,001). The frequency of the heterozygous RsaI AG-genotype was three times higher in infertile smokers (23,8 vs. 7,4%; P = 0,038) compared with infertile nonsmokers and nine times higher in azoospermic smokers (66,7 vs. 6,9%; P = 0,035), compared with azoospermic nonsmokers. The RsaI polymorphism in the ER gene may have modulating effects on human spermatogenesis. There seems to be consistent association between RsaI polymorphism and smoking habits in infertile men.